2012
DOI: 10.1001/archgenpsychiatry.2012.513
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and the Neural Processing of Facial Emotions in Adults With Autism

Abstract: Modulation of the processing of facial expressions of emotion by serotonin significantly differs in people with ASD compared with control subjects. The differences vary with emotion type and occur in social brain regions that have been shown to be associated with group differences in serotonin synthesis/receptor or transporter density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 88 publications
(95 reference statements)
7
46
0
Order By: Relevance
“…Some previous studies have shown that people with ASD have difficulty differentiating emotional from neutral faces (Dalton et al, 2005), whereas others have observed small, non-significant differences in the recognition of neutral faces (Lindner & Rosén, 2006), although samples have generally been small. Despite, on average, high levels of intelligence among our ASD sample, participants were significantly less adept at understanding whether an emotion was present in a given facial expression, which may be the result of differential attention to facial features (Pelphrey et al, 2002) and neural abnormalities in social-cognitive structures involved in emotion (Daly et al, 2012) and face processing (Pierce, Müller, Ambrose, Allen, & Courchesne, 2001). …”
Section: Discussionmentioning
confidence: 87%
“…Some previous studies have shown that people with ASD have difficulty differentiating emotional from neutral faces (Dalton et al, 2005), whereas others have observed small, non-significant differences in the recognition of neutral faces (Lindner & Rosén, 2006), although samples have generally been small. Despite, on average, high levels of intelligence among our ASD sample, participants were significantly less adept at understanding whether an emotion was present in a given facial expression, which may be the result of differential attention to facial features (Pelphrey et al, 2002) and neural abnormalities in social-cognitive structures involved in emotion (Daly et al, 2012) and face processing (Pierce, Müller, Ambrose, Allen, & Courchesne, 2001). …”
Section: Discussionmentioning
confidence: 87%
“…The results from these studies suggest an atypical approach to the processing of emotion from faces in ASD. Moreover, findings of greater activity in visual processing areas in ASD during explicit emotion recognition (Daly et al, 2012;Hadjikhani et al, 2009;Hubl et al, 2003;Kleinhans et al, 2010;Loveland, Steinberg, Pearson, Mansour, & Reddoch, 2008;Silani et al, 2008), indicate that these individuals may rely on rule-based, 'disembodied' explicit emotion processing strategies, possibly of visuo-perceptual origin (for a comprehensive review on the topic, see Winkielman, McIntosh, & Oberman, 2009). Such strategies may include noticing the widened eyes in fearful expressions, leading to recognition of the emotion and consequently triggering an emotional reaction, rather than a direct and more immediate internal simulation of the emotion.…”
Section: Introductionmentioning
confidence: 99%
“…Also, our proof-of-concept studies showed abnormalities in striatal glutamate concentration in both rodent models and adults with ASDs that are linked with abnormal functional connectivity and symptom severity (Horder et al, 2013). Further, we reported that some brain functional anomalies can be reversed in ASDs (and even in adults) by targeting serotonin (Daly et al, 2012(Daly et al, , 2014. In parallel, we identified several new risk factors-e.g., we showed that father's age significantly increases the risk for ASDs (and schizophrenia) by increasing the rate of de novo copy-number variants (Kong et al, 2012).…”
mentioning
confidence: 60%